Tecnologias da indústria 4.0 e a distribuição regional no Brasil (1997-2019) - Santos, Anelise Peixoto dos, 1995- (2023)
Orientadores: Antônio Carlos Diegues, Renato Garcia, Suelene Mascarini de Souza Romero